Management outcome of obstructed kidney disease due to stones: experience from Gezira hospital for renal disease and surgery, Sudan - Fadol, Nadir I A; Mohammed, Mohmmed E; Taha, Sami M; Gismalla, Mohamed D Awadalla (International Journal of Medicine, 2017)
Background: Obstructive nephropathy which caused by stones is a burden problem in developing countries associated with late presentation and a lot of complications.Objective: This study was done to evaluate the outcome of management of obstructed kidney due to stones at Gezira hospital for renal disease & surgery.Material and Methods: This is prospective cross-sectional hospital-based study. All patients who presented with obstructed kidneys and fulfill the criteria were included. Constructed flow chart was used to collect data. Then data was analyzed to detect the dependent & independent variable. Relation with P-value <0.05 are considered significantly.Result: 140 patients are included. Duration of Presenting symptoms was 9 weeks or more in 99 patients, 5-8 weeks in 11 patients, 2-4 weeks in 6 patients, and less than two weeks in 30 patients. It is strongly related to post-intervention serum creatinine (P-value =0.009).Common site of stone is ureter (58 patients) and renal pelvis (54 patients) significantly associated with recovery (P-value 0.009). An urgent intervention was done to 69 patients. Definitive treatments were Open surgery, endoscopic procedure (URS), or both with rate 65(46.4%), 57 (40.7%), and 10(7.2%) respectively. In 5.7% (n= 8 patients) endoscopic procedure (URS) was failed. Postoperative follow up (after 6 weeks or after removal of stent) 95.7 % (n=134 patients) were free from symptoms, and there were no clinical signs in all patients post intervention.Conclusion: late presentation and site of obstructed kidney stone can predict the complication and affect the outcome.